Fertility suppression in male Sprague-Dawley Rats by Administration of Methanolic Extract of Hempedu bumi (Andrographis paniculata) - Dayang Nurul Fatihah,; Mahanem, M.N. (Universiti Kebangsaan Malaysia, 2015)
The recent expanding rat population is causing severe economic losses and diseases in human. The main objective of this study was to evaluate the antifertility effects of Andrographis paniculata (AP) methanol extract on the weight of testis, sexual behaviour, fertility, sperm quality and serum testosterone level in treated male rats compared with control rats. A total of 21 adult male rats Sprague-Dawley aged 12 weeks were divided into three groups; control group (distilled water), low dose group (800 mg/kg) and high dose group (1600 mg/kg) of AP methanol extracts given orally for 24 days. Body and testis weight, sexual behaviour test, fertility test, sperm quality and serum testosterone level were measured. Oral administration of AP methanol extract showed a significant decrease in testis weight, number of mountings, number of fetuses, sperm count, sperm motility and serum testosterone levels for all treatment group as compared with the control group, whereas mortality showed a significant increase. Observation on testis histology of treatment group exhibited features of degeneration in Sertoli cells and germinal cells in the seminiferous tubules, followed by the shrinkage of Leydig cells as compared with the control group, which showed characteristics of normal spermatogenesis. In conclusion, AP methanol extract exhibited antifertility effects in male rats, suggesting that AP is a potential herb to be applied as rodenticide.